Here's the question you clicked on:
sarah_hendrix7
Please Help?
do you want the whole steps or just a result? the final result is an = -7 *6^n
a(n+1) -6 a(n) =0 characteristic equation is x -6 =0 x =6 the equation has the form an= C*6^n replace a1 = C *6^1 = -42 ---->C = -7 replace C into an form to get an= -7 *6^n Hope this help. are you in discrete math course?If so, you will understand what i mean
What's wrong? and what makes you laugh
@ParthKohli : I am a student and want to study from others. Please tell me if I am wrong in my work, I appreciate when you correct my mistake or my flaw
You have left a lot of space. :-)
I don't know why the net post it up. I am not good at computer
I think we can do this using the geometric sequence formula.
yes, you are right. show me your work. now is your turn
Your answer is correct anyway.
\(a_1 = -42\) and \(r = -6\). Now use the following formula:\[a_n = a_1 \times r^{n - 1}\]
Strictly speaking, if you have:\[a_{n + 1} = {\rm some ~number} \times a_n \]For all \(n\), then the "some number" is the common ratio denoted by \(r\).
I'd leave it to the asker to do the rest.
I need help from my problem, may I have yours?
Sure, what may I help you with?
my problem is: find the coefficient of x^10 in the power series of (x^2 +x^4 +....) (x^3 +x^6 +x^9 +....)(x^4 +x^8 +x^12 +....)
This is an interesting problem. Let's see.
You can just message me here; I check this site much often... more than I check my email
dealt. since I have to go. send me message when you've done. Nice to see.